Prevalence and clinical features of adverse food reactions in Portuguese adults. Issue 1 (December 2016) - Lozoya-Ibáñez, Carlos; Morgado-Nunes, Sara; Rodrigues, Alexandra; Lobo, Cláudia; Taborda-Barata, Luis
Abstract Background Only one previous study, via telephone call, on the prevalence of self-reported food allergies has been performed in Portugal, in a small sample of adults. The objective of this study was to determine the prevalence of self-reported and probable food allergy, analyze the clinical features and involved foods in Portuguese adults. Methods Population-based, cross-sectional study performed in various healthcare centres from central Portugal. All 1436 randomly selected individuals (median age: 45 years, 50.6 % female) replied to a validated food allergy questionnaire by phone. Those who reported an adverse food reaction were invited to come to the hospital, where clinical history was taken, skin prick (SPT) and prick-prick skin (SPPT) tests were performed and food allergen-specific IgE levels (sIgE) were determined. An open oral challenge was performed in selected cases. Cases of positive clinical history of immediate (up to 2 h after ingestion) reaction in association with positive food sIgE levels and/or skin prick tests were classified as IgE-associated probable food allergy. Cases of positive clinical history of delayed (more than 2 h after ingestion) and negative food sIgE levels independently of positive SPT or SPPT results were classified as non-IgE associated probable food allergy. Results The prevalence of probable food allergy in our sample was 1 %, with shellfish and fish as the most frequently implicated foods. IgE-mediated probable food allergy occurred in 0.71 % of cases, with shellfish, peanut and nuts mainly involved. Cutaneous symptoms were most frequently reported. Prevalence values and food types were discrepant between self-reported and probable food allergies. Conclusions The prevalence of probable food allergies in Portuguese adults is low, is mostly related to shellfish, peanut and nuts and most frequently involves cutaneous symptoms.